POBLACIÓN ADECUADA EN UN SISTEMA DE CÍRCULO DE CULTIVO SEMBRADO CON PLÁTANO (Musa AAB) EN ALTAS DENSIDADES EN LA EET-PICHILINGUE - Montiel Bravo, Fabian Enrique (2023)
With the objective of evaluating the agronomic and productive behavior of plantain under a high-density crop circle system, the present research was carried out at the EET-Pichilingue, located at km 5 via Quevedo-El Empalme, canton Mocache, Los Ríos, at an altitude of 120 meters above sea level. The basis of the experiment was a randomized complete block design (RCBD) with seven treatments and three replications.5 m. The results of the variables plant height, stem diameter, number of leaves, frui.